Where the world ends - McCaughrean, Geraldine (Flatiron Books, 2019)
Every summer, as per tradition, a young boy named Quill and his friends are dropped off on the shore of a large, rocky, and remote sea stac. They are there to hunt birds for a time, then someone comes by boat to pick them up. Only this summer nobody comes. The boys decide that the only explanation is that the world has ended, and they are on their own, cold, starving, clinging to just a large hunk of rock in the middle of the ocean. Somehow, they must find a way to survive in a place forsaken.